(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the outcome of the outcome between auto refraction and subjective refraction in patients. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi from March 2019 to February 2020. Materials and Methods: A cross-sectional study was conducted on 120 patients above 15 years of age. Topcon (RM8800) was the auto refractor used to determine auto refraction, whereas subjective refraction was carried out using a trial frame in which spherical lenses were inserted. Each eye was checked monocularly, and then binocularly, with all eye measurements carried out without cycloplegia. SPSS was used to evaluate data, and for comparison, a paired t-test was applied with a P-value set at ≤0.05. Results: The mean spherical equivalent difference between auto refraction and subjective refraction of both eyes was (±0.17D±0.12D). The p-value of the right eye and left eye between auto refraction and subjective refraction was found to be (0.033-0.088), which is statistically significant. Conclusion: Study confirms the variation between subjective refraction and auto refraction. Auto refraction is satisfactory for preliminary refraction but is not deemed satisfactory as substitutes for conventional subjective refraction.